2014
DOI: 10.1007/978-3-642-55355-4_17
|View full text |Cite
|
Sign up to set email alerts
|

Process Oriented Dependency Modelling for Service Identification

Abstract: Part 3: Finance and Service ScienceInternational audienceService-Oriented Architecture (SOA) is important for organisations to achieve dynamic business process and build business agility. One of the first step for service oriented applications implementation is to properly identify a set of fine-grained services. A right service granularity is necessary to satisfy lower coupling and higher cohesion principles for reusable software services. To meet this challenge, a lot of efforts have been attached to support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…At a general level, in service engineering, the identification of services plays a fundamental role, as it establishes the basis for subsequent processes (Rong et al, 2014). Identification of ITS is one of the most important activities in the construction process of the ITSC and also of the ITSCM; in fact, several studies have focused on this topic (Mera & Aguilar, 2019).…”
Section: Its Identificationmentioning
confidence: 99%
“…At a general level, in service engineering, the identification of services plays a fundamental role, as it establishes the basis for subsequent processes (Rong et al, 2014). Identification of ITS is one of the most important activities in the construction process of the ITSC and also of the ITSCM; in fact, several studies have focused on this topic (Mera & Aguilar, 2019).…”
Section: Its Identificationmentioning
confidence: 99%
“…As mentioned above, in service engineering, the identification of services plays a fundamental role, since it establishes the basis for subsequent processes [5]. A study by Souza et al [22] showed that the methods of analysis and the design of services aim to identify services and organize them into a manageable hierarchy of compound services to support the processes carried out by a company.…”
Section: The Process Of Identifying Itssmentioning
confidence: 99%
“…In service engineering, the identification of services plays a fundamental role since this identification establishes the basis for subsequent processes [5]. Then, if the services are poorly identified, these subsequent processes are negatively influenced [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation